Entrepreneurship development potential of perennial forages under rainfed semi-arid central India: a case study - Palsaniya, D R; Kumar, T Kiran; Rai, Suchit K; Choudhary, Mukesh; Kumar, Sunil (Indian Farming, 2019)
Perennial grasses like Napier Bajra hybrid, guinea and tri specific hybrid are important source ofround the year green fodder. Their demand is increasing in recent year particularly from dairyfarmer, peri-urban milkshed area, Gaushala, forest department, NGOs, etc. Farmer can plantrooted slips of the forage in July, take fodder for the whole year and then sale rooted slips in nextJuly and August to get higher return. The paper assessed the multiplication behaviour, fodderproduction and entrepreneurship development potential of perennial forage crop under rainfedsemi arid central Indian condition in this case study.